GREEN OPEN SPACE MANAGEMENT STRATEGY FOR RECREATION IN DKI JAKARTA - Oktovianus; OKTAVIA, RENO CATELYA DIRA; Siregar, Hermanto; Hermawan, Rachmad; Sunarminto, Tutut (Media Konservasi, 2023)
Cities are dominated by two closely related aspects, namely the physical and human aspects. The physical aspect exists naturally in the form of space and its elements, while the human aspect is the subject of development as well as the user of its benefits. The city is part of human settlement, in its development, there is disintegrated planning because its development approach only sees the city as a physical object rather than a cultural object. The modern lifestyle requires the environmental atmosphere to be natural environmental atmosphere, which is valuable. The study was conducted to calculate the contribution of the environmental services aspects of Green Open Space (RTH) as a scientific basis in the policy strategy for managing Urban Parks (TK) and Urban Forest Parks (THK). Based on the results of this study, urban residents need UP and UFP as places for their recreational needs. The policy strategy is to create an appropriate GOS for recreational places. The engineering aspect of recreation sites in UP and UFP aims to optimize the recreational carrying capacity. The policy to overcome the problem improves ecological management through the enrichment and rejuvenation of old plants. Key words: Environmental Services Aspect, Green Open Space, Urban Forest Park, Urban Park